Air Canvas Application using OpenCV and NumPy - Dr. Madhur Jain,; Dr. Shilpi Jain,; Mr. Ankush Kumar,; Ms. Simran Verma, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
For a very long time, written communication has been a vital tool for sharing knowledge and ideas. Both handwriting and typing are still common ways to record information in the current digital era. However, developments in wearable technology and computer vision have enabled new possibilities, such as generating text in the air with hand or finger gestures. This study presents an Air Canvas system that uses fingertip tracking to convert hand movements into real-time writing. The system uses computer vision techniques to process motion data and generate visible drawings or text. Digital messaging, education, and accessibility tools for people with physical or hearing impairments are just a few of the many potential uses for it.